Medical and nursing students’ attitudes toward mental illness: An Indian perspective - Poreddi, Vijayalakshmi Poreddi; Thimmaiah, Rohini; BadaMath, Suresh (Investigación y Educación en Enfermería, 2017)
Objective. Compare the attitudes toward mental illness between medical and nursing undergraduate students from a university in India. Methods. A cross sectional descriptive study was carried out among medical (n=154) and nursing undergraduate students (n=168) using Attitude Scale for Mental Illness (ASMI) questionnaire with six sub scales namely; Separatism, Stereotyping, Restrictiveness, Benevolence, Pessimistic prediction and Stigmatization. This was a 5-point Likert scale with 34 items to rate participants responses from totally disagree (1) to totally agree (5). The lower scores indicate positive attitudes toward persons with mental illness. Results. Our findings revealed that 54.5% of medical students versus 64.8% of nursing students have positive attitudes toward mental illness. While medical students have better attitudes against separatism and stigmatization, nursing students have more positive attitudes in benevolence and against pessimism. Conclusion. An important proportion of medical and nursing students have negative attitudes toward mental illness. It is necessary to review and adapt the current curriculum to favor the positive attitude of future professionals toward people with these types of diseases. How to cite this article: Poreddi V, Thimmaiah R, Math B,S. Medical and nursing students’ attitudes toward mental illness: An Indian perspective. Invest. Educ. Enferm. 2017; 34(1):